The role of the seed coat in adaptation of dimorphic seeds of the euhalophyte Suaeda salsa to salinity. Issue 2 (21st April 2016) - Song, Jie; Shi, Weiwei; Liu, Ranran; Xu, Yange; Sui, Na; Zhou, Jiachao; Feng, Gu
Abstract : The role of the seed coat in adaptation of dimorphic seeds of the euhalophyte Suaeda salsa to salinity was investigated during germination and early seedling growth. Black and brown seeds were treated with chloroform for 1 min before the extract was used to analyze waxes and the seeds to investigate the protective role of the seed coat under saline conditions. Waxes in black seed coats were more abundant than those in brown seed coats. Salinity (500 mM NaCl) increased the concentration of Na + and decreased the concentration of K + in both black and brown seeds regardless of chloroform treatment. Chloroform treatment alone (in the absence of NaCl) had no effect on the concentration of Na + or K + in black or brown seeds and in the presence of 500 mM NaCl had no effect on the concentration of Na + or K + in brown seeds. However, chloroform treatment increased Na + and decreased K + in black seeds with 500 mM NaCl. A change of MDA (malondialdehyde) concentration in black and brown seeds treated with or without chloroform was similar to the change of Na + concentration. High salinity (1500 mM NaCl) pretreatment for 40 days had a less adverse effect on germination of black seeds compared with brown seeds after they were transferred to fresh water regardless of chloroform treatment. Similar results were found for seedling emergence. In conclusion, a black seed coat may be more protective than a brown seed coat, probably by shielding the embryo from ion toxicity, because of its higher content of waxes. Thus black seeds can better maintain seed viability than brown seeds for extended periods under hypersaline conditions. Abstract : 1. A black seed coat may be more protective than a brown seed coat, probably by shielding the embryo from ion toxicity, because of its higher content of waxes. 2. Black seeds can better maintain seed viability than brown seeds for extended periods of times during exposure to hypersaline conditions. This trait of dimorphic seeds can help S. salsa to build up its population in variable saline environments.